Rejection of the monotypic status of Peromyscus furvus (Rodentia: Cricetidae), with consequences for its species group - Cruz-Gómez, Alejandro; Castro Campillo, A. Alondra; Ávila-Valle, Zamira A.; León-Paniagua, Livia; Ramírez-Sánchez, Marcia; Ramírez-Pulido, José (THERYA, 2021)
Previous studies using Cytochrome-b or ND3-ND4 mitochondrial gene have yielded intriguing evidence about the phylogenetic relationships among populations of Peromyscus furvus; however, those studies each based on phylogenies for a single type of genes, yielded conflicting topologies. In addition, analyses with traditional morphometrics have revealed differences in skull size among certain populations of the species. Therefore, in order to reassess the systematic and taxonomic status of P. furvus, we incorporated a suite of genetic and morphometric characters and employed cladistic analyses. Herein, we present results mostly derived from our genetic analyses (results from the phylogenetic examination of skull size and shape will appear later). Phylogenetic analyses were conducted using four mitochondrial genes (Cytb and ND3-ND4L-ND4) with the respective data analyzed separately or combined, followed by an analysis with genetic and morphometric data (size and shape characters). Most phylogenetic constructions were made with parsimonious methods, but probabilistic methods also were used in the analyses with the genes separated by type. Similar topologies were recovered from all analyses of the Cytb gene and from all parsimony analyses of the NADH genes; however, conflicting topologies were obtained with the probabilistic methods for the NADH genes. Additionally, to better understand the genetic variation in each type of gene, analyses for genetic divergence were conducted within and among genetic groups and haplotype networks were constructed. All the topologies obtained using genetic data questioned the monotypic status of P. furvus, as two additional clades were identified that seemingly correspond to unrecognized entities. The first of these, P. latirostris, occurs in the northern region and could be considered as either a species or subspecies. An unknown Peromyscus species nova that occurs to the south is considered as a valid species. Further, P. furvus s. s. becomes a polytypic species by recognizing at least two subspecies (P. f. angustirostris and P. f. furvus). Phylogenetic analyses also rejected membership of P. melanocarpus and P. ochraventer within the furvus species group. Instead, P. melanocarpus showed a greater affinity to P. mexicanus totontepecus, whereas, P. ochraventer either joined to the clade containing P. melanocarpus and P. m. tototepecus or to Megadontomys cryophilus in a sister clade. Finally, Osgoodomys banderanus (subgenus Haplomylomys) always remained basally positioned and segregated from all members of the subgenus Peromyscus.